Wealth of Experience :Real investors on what works and what doesn't - The Vanguard group - S. Clarke Andrew (John Wiley & Sons, 2003)
"There are many paths to investment success, but few are as straight and true as Vanguard’s. Simplicity, thrift, and broad diversification are powerful allies. Andy Clarke has assembled a wealth of real-world examples that will show you how to get these forces working in your favor."